PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM KASUS PENIPUAN TRANSAKSI E-COMMERCE - Al Farizy, Salman (Jurnal Hukum Positum, 2024)
This research discusses the legal protection of victims of fraud in online buying and selling transactions, a form of cyber crime that is increasingly prevalent along with the development of e-commerce. These scams often take advantage of anonymity and regulatory loopholes, resulting in financial losses and difficulty in identifying the perpetrators. The research uses a phenomenological qualitative approach with literature review and case analysis to explore the phenomenon of electronic transaction security and its impact on consumers. The results show that fraud in online transactions in buying and selling has legal consequences, both criminal and civil, with law enforcement still facing challenges, such as lack of digital literacy, limited regulations, and weak cyber infrastructure. Here the author further recommends increasing digital education, strengthening e-commerce regulations, and developing a more secure system on digital platforms. In addition, the importance of the precautionary principle in online transactions on trusted platforms is the main focus to minimize the risk of fraud in online buying and selling transactions. This research contributes to understanding and overcoming legal problems in electronic transactions in the digital era.